Influence of impurities in propane coolant on the process of obtaining artificial cold - Larycheva, Liudmyla; Lutsenko, Oleh; Chernenko, Yana; Voloshyn, Nikolay (Eastern-European Journal of Enterprise Technologies, 2017)
The study of the influence of propane quality on the total pressure of vapors of the coolant in condensation and vaporization processes and on operation of refrigeration equipment was carried out. Research was carried out in the refrigeration department of the industrial combined unit of deparaffination of raffinates and oil removal from gatch. In the experiment, technical propane with the content of the main component of 91–96 % by weight was used as the coolant, the rest was made up by hydrocarbon impurities. To determine the composition of the coolant, chromatographic method for separation of hydrocarbons was used. The impact of propane quality on total pressure of coolant vapor in the refrigeration cycle was determined. Impurities were found to contribute to an increase in total pressure and temperature in evaporation and condensation processes. A decrease in propane content in the coolant from 95 % by weight to 89 % by weight leads to an increase in pressure in condensers from 57 to 86 kPa, in condensers – from 1,385 to 1,524 kPa. At the same time, there is an increase in temperature of evaporation and condensation by 4–5 oС. Contribution of each separate impurity to total pressure of saturated vapors of the coolant in evaporators and condensers was determined. The most harmful impurities are ethane and butane. Ethane and methane under conditions of cold production are in gaseous state and increase total pressure in the refrigeration cycle. The content of methane in the raw material mixture does not exceed 0.03 % by weight, which is why its impact on total pressure is negligible. Butanes form a liquid film on the surface of the equipment, worsen heat exchange processes, and contribute to an increase in the total pressure. Propylene behaves in the system as a coolant and its impact on total pressure is insignificant. The impact of hydrocarbon impurities on operation of refrigeration department was established. The impurities differently affect operation of the equipment, however, on the whole, this impact is negative. An increase in amount of impurities in the coolant contributes to an increase in power consumption of the compressor, worsens compression process and increases consumption of electricity. A decrease in propane content in the raw material mixture from 97 % to 95 % leads to an increase in total thermal loading on the condenser and the refrigerator by 1.7 %. This causes additional material and energy consumption in the course of cold production